Impact of Leverages on Profitability: A Case Study of Coramondal Fertilisers Ltd - Sam Luther, C. T. (Indian Journal of Finance, 2008)
The term 'leverage' may be defined as the percent of change in one variable by the percent of change in some other variable or variables. In finance, the term leverage is used to describe the firm's ability to use fixed cost assets or funds; the former is popularly known as 'operating leverage' and the latter is known as 'financial leverage'. Greater of these leverages means higher the returns to the equity shareholders. This paper focuses on the impact of operating and financial leverages on the profitability of Coramandal Fertilisers Ltd, a leading fertiliser manufacturing firm from South India.